Los Maestros en el ojo del huracán: Guerra Civil y Franquismo. Teachers in the eye of storn. Spanish Civil War and Franco's regime. - Jesús Gutiérrez Flores (Cabás)
(ES) El debate sobre la educación ha sido y sigue siendo el objeto de debate que ha recorrido la Historia de España contemporánea. La mayor apuesta por la educación se centra en los años de la Segunda República. El objetivo era conseguir a través de la formación un país más culto, más moderno y europeo. Pero esta visión tan loable de la educación se hacía a costa de la prohibición de la enseñanza de las órdenes religiosas. El franquismo arroja la culpa de los males del país a la enseñanza impartida por los maestros republicanos a los que considera disolventes y contaminados por ideas perniciosas importadas del extranjero. (EN) The debate over education has been and remains a controversial subject that has travelled through the contemporary history of Spain. The greater commitment to education is found on the years of the Second Republic. The goal was to get a more cultured and more modern and European country thankss to an important bet on education. But this laudable vision of education was done at the expense of the prohibition of the teaching by people belonging to religious orders. For that reason, in Franco´s regime the blame for the country's troubles is put on the education provided by the Republican teachers who were considered impregnated by pernicious ideas imported from abroad.